Situating Statutory Interpretation in its Public Law Context - Janina Boughey; Lisa Burton Crawford (Legal Education Review)
Law teachers have debated whether teaching statutory interpretation as a distinct body of law requires that it be taught as a stand-alone subject, or whether it is best to ‘embed’ statutory interpretation within other subjects. There are benefits and problems with both approaches. In addition, there is the question of where in a degree to place a unit on statutory interpretation. In this paper we argue that statutory interpretation can be seen as a distinct and core component of public law. We argue that it is different to, but interconnected with, the other public law subjects of constitutional and administrative law. As such, we suggest that one method of teaching statutory interpretation is to teach it alongside foundational public law concepts and principles in a first-year unit. In our experience, teaching statutory interpretation in this way overcomes several of the common challenges that academics have reported in teaching statutory interpretation.